Contemporary approaches to the diagnosis and management of Pancreatic Ductal adenocarcinoma, examining the role of biomarkers in aiding early diagnosis - MATTHEW MORTIMER (2024)
Whilst other cancers have seen improvements in survival over recent decades, Pancreatic Ductal Adenocarcinoma (PDAC) remains a disease with poor outcomes. At present no screening tests exist to detect pancreatic cancer at an early stage in the asymptomatic population. There is an increasing interest in novel ways to detect pancreatic cancer at an earlier stage in the disease process when a potential cure is more likely to be achieved. A literature review was undertaken of the current understanding and management of this devastating disease, focussing on aetiology, current methods of cancer diagnosis and staging, and therapeutic options. A feasibility study was then undertaken to evaluate the diagnostic accuracy of a selection of novel candidate biomarkers to differentiate between plasma and urine obtained from participants with and without pancreatic cancer, comparing them with the current gold standard biomarker, Ca19-9, which is often used with a cut-off concentration of 37U/L. Enzyme-Linked-Immunosorbent Assay (ELISA) was used to quantify concentrations of Ca19-9, Thrombospondin-2 (THBS2) and Human Chitinase 3-like 1 (YKL-40). Samples were analysed using Fourier Transform Infrared (FTIR) spectroscopy, with the spectra of cancer and non-cancer specimens being compared, allowing a machine-learning diagnostic model to be created. In isolation, plasma Ca19-9 had the greatest ability to discriminate between cancer and non-cancer (AUC = 0.885). However, a multi-analyte panel (comprising plasma Ca19-9, plasma THBS2 and urinary THBS2) was found to have a greater diagnostic accuracy to discriminate between the 2 groups when compared to using the widely used Ca19-9 cut-off of 37U/L (83.33% vs 76.6%). A diagnostic model using FTIR spectroscopy had a diagnostic accuracy of >90%.Pancreatic cancer remains a disease with poor outcomes, but there are promising new strategies to diagnose patients at an earlier stage. The initial results from these investigations are promising, but require validation with a larger test cohort.